Kesalahan Penggunaan Bahasa Indonesia dalam Ruang Publik (Media Luar Ruang) di Kota Baubau - Nazriani Nazriani; Arsad Arsad (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2020)
The influence of foreign languages, especially English may erode Indonesian authority. Most people feel more confidence and smarter when using English. It is not wrong but contradict to the slogan echoed by the government, "Prioritizing Indonesian, mastering foreign language, and Preserving the language”. This research was aimed to study about how the forms of improper use of Indonesian in public spaces in Baubau, and what were the factors that influence the occurrence of these errors. The methods used descriptive qualitative. Technique of collecting the data was used observation and technical documentation record. The result showed that the errors found are errors in placing prefixes and prepositions which still confused-exchange as well as the widespread use of English on shop signs, hotels, salons, and other general instructions. Some of the factors triggering the occurrence of these errors is the lack of knowledge about the use of the Indonesian language properly and correctly, lack of socialization that involve direct community of language users, and the absence of real sanctions for violators language. The results showed that the form were errors in placing prefixes and prepositions are still confused-exchange as well as the widespread use of English on shop signs, hotels, salons, and other general instructions. Some of the factors triggering the occurrence of these errors is the lack of knowledge about the use of the Indonesian language properly and correctly, lack of socialization that involve direct community of language users, and the absence of real sanctions for violators language. Based on the research results form errors found are errors in placing prefixes and prepositions are still confused-exchange as well as the widespread use of English on shop signs, hotels, salons, and other general instructions. Some of the factors triggering the occurrence of these errors is the lack of knowledge about the use of the Indonesian language properly and correctly, lack of socialization that involve direct community of language users, and the absence of real sanctions for violators language.